Epidemiological and clinicobacteriological study of neonatal sepsis - M., Dhivyanarayani; V., Raju; K., Vindyarani W. (International Journal of Contemporary Pediatrics, 2018)
Background: Neonatal mortality is still high in developing countries like India, which is mostly contributed by sepsis. Early diagnosis and appropriate management can improve the outcome of neonatal sepsis. Diagnosis of neonatal sepsis can be difficult at times as the symptoms and signs are nonspecific. To study the incidence of sepsis in different gestational age and birth weight categories. Methods: The study conducted prospectively in1169 babies admitted to NICU from first May 2011 to 30th April 2012. Data was collected using performance. Investigations including CBC, CXR, Blood culture sensitivity and CRP were done on the same day (IT ratio and micro ESR were not done). CSF study and cultures of urine, surface swab, tracheal aspirate etc done only in selected cases. Results: There were 238 episodes of sepsis and the incidence of sepsis in this study was 20.01% among the babies admitted during the study period. The incidence was more in extreme preterm and extremely low birth weight categories. Among babies with sepsis culture positive sepsis was seen in 18.45%. E. coli was the commonest organism in EOS and Klebsiella in LOS. Conclusions: In this study incidence of neonatal sepsis was 20.35%. Lower the birth weight and gestational age, higher was the incidence of sepsis. PROM >18 hours, MSAF and prematurity were found to be associated with EOS while extreme prematurity, prolonged ventilation, indwelling catheters and prolonged hospital stay were found to be statistically significant in causing LOS.